The influence of leadership modes on the success of strategic change programs: case of high ranked Algerian Universities - SAlhi Maroua (msila university, 2024)
This thesis examines the impact of different leadership styles on the success of change programs through a field study involving interviews with deans and managers at Skikda University. The researcher employed an interpretive approach, focusing on understanding experiences and surrounding contexts through qualitative data collection and analysis. Results revealed that democratic, resonant, digital, and directive leadership positively influence the success of change programs by enhancing inclusivity, resolving conflicts, improving communication, and encouraging dialogue. Conversely, authoritarian and cross-cultural leadership were limited to specific applications, while paternalistic leadership provided support for personal and contextual dimensions. The study also highlighted factors contributing to effective leadership styles, such as improving relationships among stakeholders, fostering innovation and initiatives, relying on a consultative approach, and ensuring quality work and adherence to deadlines. The thesis offers valuable insights into how leadership strategies can be directed to achieve positive outcomes in implementing change programs, thereby enhancing academic performance and overcoming organizational challenges.